KESENJANGAN IMPLEMENTASI KEBIJAKAN DIGITAL DALAM LAYANAN HAK TANGGUNGAN ELEKTRONIK: ANALISIS INTEGRASI SISTEM DAN KAPASITAS ORGANISASI DI KANTOR PERTANAHAN KABUPATEN BANDUNG - Indra Aditya Prayoga; Putri Indah Caturi; Ami Priatna; Ridha Rahim Al'libani; Fitri Mustika Madliah Munawaroh (Jurnal Progress Administrasi Publik, 2026)
Digital transformation in public service delivery requires alignment between technological system integration and organizational capacity to ensure effective policy implementation. This study aims to analyze policy implementation gaps in Electronic Mortgage Services (HT-el) at the Bandung Regency Land Office, focusing on the interaction between system integration and organizational capacity. A qualitative case study approach was employed using in-depth interviews, observations, and document analysis. The findings reveal that HT-el implementation remains suboptimal due to misalignment between digital systems and organizational capacity, reflected in a significant increase in service delays in 2025. Key factors include ineffective policy communication, limited resources, resistance to digital systems, and fragmented bureaucratic structures. The analysis demonstrates that implementation gaps are not solely driven by technological limitations but arise from complex interactions within a socio-technical system. This study contributes to the literature by positioning system integration and organizational capacity as key determinants of digital public service effectiveness.   Keywords: Digital Government; Electronic Mortgage; Organizational Capacity; Policy Implementation; System Integration